2016
DOI: 10.1080/21505594.2016.1213476
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem for treating KPC-producing Klebsiella pneumoniae bloodstream infections: Should we get to the PK/PD root of the paradox?

Abstract: The objective of this study was to assess the achievement of pharmacokinetic/pharmacodynamic (PK/PD) targets of meropenem (MEM) in critically-ill patients with bloodstream infections (BSI) due to Klebsiella pneumoniae-carbapenemase-producing Klebsiella pneumoniae (KPC-Kp) with MEM minimum inhibitory concentrations (MICs) ≥16 mg/L. Nineteen critically-ill patients with KPC-Kp BSI were given combination therapy including MEM, tigecycline, plus colistin or gentamicin (according to susceptibility testing). MEM was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 38 publications
(66 reference statements)
2
11
0
1
Order By: Relevance
“…These data suggest that meropenem would be ineffective when the strain exhibits high-level resistance. In fact, meropenem (2 g every 8 h in extended infusion) did not reach any pharmacokineticpharmacodynamic target in 19 patients with infections due to KPC-producing K. pneumoniae with meropenem MICs of Ͼ16 mg/liter in a recent study (16). Additionally, a recent study found a higher rate of failure for the carbapenem-colistin combination in patients with KPC-producing K. pneumoniae bacteremia caused by isolates highly resistant to colistin and doripenem (17).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that meropenem would be ineffective when the strain exhibits high-level resistance. In fact, meropenem (2 g every 8 h in extended infusion) did not reach any pharmacokineticpharmacodynamic target in 19 patients with infections due to KPC-producing K. pneumoniae with meropenem MICs of Ͼ16 mg/liter in a recent study (16). Additionally, a recent study found a higher rate of failure for the carbapenem-colistin combination in patients with KPC-producing K. pneumoniae bacteremia caused by isolates highly resistant to colistin and doripenem (17).…”
Section: Discussionmentioning
confidence: 99%
“…This means that screening approaches in these settings should include broth microdilution methods (29,30), with a cutoff MIC for meropenem of 64 mg/liter (14). This may allow identifying the proportion of strains with an MIC of Յ64 mg/liter for meropenem, whose frequency may vary greatly from hospital to hospital (13,31,32). It is worth noting that the frequency was as high as 89.3% among the 169 KPC-Kp clinical isolates included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Tumbarello et al (4) and Daikos et al (9) support the supposition that an EI of meropenem at 6 g/day may work in these cases, with a higher mortality rate when MICs are higher. The possibility that this approach might be feasible even against KpC-Kp infections due to strains with higher meropenem MICs is still to be demonstrated (12,13). In this regard, we recently showed that high-dose CI (HDCI) meropenem, in combination with other antimicrobials with activity against Gram-negative bacteria, was effective in the treatment of KPC-Kp infections (mainly of the bloodstream) due to strains with a meropenem MIC of up to 64 mg/liter (14).…”
mentioning
confidence: 99%
“…However, it is controversial to use %T ϾMIC (40%) as the target. It was reported in the clinical study that %T Ͼ4MIC should be over 40% to achieve clinical success (25,26). This study showed meropenem 2 g with 8-h infusion (%T ϾMIC , 90%) combined with colistin did not show better efficacy at 24 h compared with 3-h infusion (%T ϾMIC , 51%) using apparent MIC calculation for each regimen.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, the maximum concentrations of meropenem regimen with 1 g and 2 g with 3-h prolonged infusion reached 16.5 and 32.9 mg/liter (24). It is very hard to achieve the PK/PD target for the highly resistant strains with an MIC of Ն32 mg/liter (25). The synergistic combination therapy can decrease the apparent MICs of both antibiotics and, therefore, increase the possibility of reaching targets for A. baumannii.…”
Section: Discussionmentioning
confidence: 99%